Persaingan Bisnis Antar Minimarket Dan Grosir Eceran Dalam Perspektif Bauran Pemasaran Islam : Studi Kasus di Jalan Pancing Kota Medan - Silfira Ayu Ningsih Pasaribu; Imsar Imsar; Atika Atika (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to analyze business competition and the suitability of the marketing mix between minimarkets and retail wholesalers from an Islamic perspective. This research uses a descriptive qualitative approach with interviews. The results of this research show competition between minimarkets and retail wholesalers in the marketing mix. If you look at it from a product perspective, mini markets sell various types of products, while wholesalers are more limited. And in terms of price, minimarkets sell at more expensive prices than wholesalers. And in terms of promotion, minimarkets are more attractive than wholesalers. Second, the suitability of the marketing mix, business competition between minimarkets and retail wholesalers from an Islamic perspective. The products sold by minimarkets and wholesalers are halal certified. Price determination is in accordance with the quality and added value of each product and in accordance with Islam. In a business, honesty is very important in Islam and must be implemented well. In Islam, a place of business can be set up anywhere as long as the place is not in dispute.